PELESTARIAN VEGETASI LOKAL DALAM RANGKA PENGEMBANGAN TATA RUANG KEPULAUAN SERIBU (Conservation of Local Vegetation in the Space Development of Kepulauan Seribu) - Nyoto Santoso (Media Konservasi, 2005)
Condition of vegetation land in Kepulaun Seribu is very needed as a life supporting system, particularly water balance and freshwater resource for local community. Beside that, it is very important for habitat of wildlife and water biota. Conservation and management of vegetation land or green space reserve in Kepulauan Seribu is not denied by decision maker.